Quality of fermented foods (Experimental biology, 2015)
Fermentation is, with drying and salting, one of the oldest methods for food preservation. Fermented foods can represent more than half of the daily diet of rural and urban populations in many countries in the world. The processes participating to the elaboration of the quality of fermented foods depend on the composition of the raw material and of the indigenous microflora but also of the environmental conditions of the raw material. Generally, pre-fermentative operations allow bacterial species (i) to colonize mainly the environment, (ii) to lead specific biochemical transformations catalyzed by enzymes synthesized in a sufficient quantity and active, (iii) to synthesize macromolecules with antimicrobial activity.